Land use and cover and its relationship with water quality and availability in the Ribeira de Iguape e Litoral Sul watershed - Adrien , Pedro Vitor Soares; Delgado, María Isabel; Américo-Pinheiro, Juliana Heloisa Pinê (ANAP Brazil, 2025)
ABSTRACT Objective – To analyze the land use and cover of the Ribeira de Iguape and Litoral Sul watershed and its relationship with water availability and water quality Methodology – Literature review with searches in articles from scientific journals and periodicals, as well as the use of technical reports from public bodies. The "MapBiomas" platform was used to search for information on land use and cover. Originality/Relevance – The diagnosis of the situation of land use and cover and water resources is of great importance, allowing the identification of threat points for the conservation of natural resources. The topic gains even more relevance for the Vale do Ribeira region, which contains about 11,800 Km² of the Atlantic Forest Biome, the largest remnant in the state of São Paulo and one of the largest in Brazil. Results – The watershed has an extensive remnant area of the Atlantic Forest biome (40% of the state of São Paulo) and reduced industrial activities and demands for water permits. These factors, added to the high rainfall indices (annual average of 2,185 mm), result in water in quantity and quality for the population of the region. Theoretical/Methodological Contributions – The use of the "MapBiomas" platform combined with the use of technical reports from public bodies was effective for carrying out the study, and can be adopted for the diagnosis of other hydrographic basins. Social and Environmental Contributions – The survey of information on the hydrographic basin allowed the identification that the region suffers from socioeconomic problems, with an HDI below the state average of São Paulo (0.711) and negative growth rates in some municipalities, indicating a population exodus given the reduced employment opportunities. On the other hand, the low anthropogenic pressure is beneficial for the conservation of water resources and for the preservation of the Atlantic Forest Biome.